Construction of symbiosis corridors for heritage resources and optimization of conservation strategies in the basin: A case study of the Yellow River basin in Shandong, China - Ying Yu; Bin Yu; Xinwen Zhang; Lin Ma; Caijun Zhao; Yanyan Jia; Shujun Hou; Xin Han; Kun Li; Xinchuang Chen; Chuanrong Li; Bing Liu (Ecological Indicators)
There is an international consensus that the conservation of heritage resources (HRs) should be based on spatial integration. However, significant gaps still remain in the effective integration of HRs into natural environmental networks, particularly in achieving regional synergies and holistic ecological and cultural conservation in alignment with the UN Sustainable Development Goals (SDGs). The study focuses on the Yellow River Basin in Shandong (YRB-SD) applying ecosystem services (ES), morphological spatial pattern analysis (MSPA) and the comprehensive evaluation model (CEM) to identify source areas. Symbiotic corridors (SCs) are constructed using the circuit theory approach and further optimized by integrating ecological protection redlines (EPR), agro-cultural heritage (ACH), and scenic areas (SA) to enhance spatial resource interaction and improve corridor connectivity. Ultimately, 395 SCs are identified, with network connectivity increasing by 31.58 % (α: 0.35 → 0.63, β: 1.68 → 2.23, γ: 0.57 → 0.75). An operational framework of “element linkage (spatial coupling of ecological and cultural elements with networked corridor connections)—technological empowerment (remote sensing monitoring, GIS spatial visualization, VR virtual display, etc.)—multi-party synergy (collaboration among governments, communities, and multiple stakeholders)” is proposed, and the multifunctional conservation strategies of “one circle, two screens, three axes and four zones” are established. The study innovatively incorporates ACH as a symbiotic source, refines the source area extraction methodology, contributes to the achievement of the SDGs, and promotes public understanding of the joint “Connecting Practice” project. It also provides new methods and perspectives for the integrated conservation of heritage resources in the developing countries.